A. Boissière, L’Art et le vivant du jeu, Presses Universitaires de Liège, Liège 2023 (Itinera, 2024)
Anne Boissière’s last book, L’Art et le vivant du jeu inscribes the study of the experience of playing within a methodological challenge: to take seriously the “aisthetic” nature of philosophical inquiry, namely its emergence from our “way of feeling”. Offering descriptions rather than definitions, perspectives rather than theories, Boissière undertakes a philosophical “gesture” which, instead of imposing a “conceptual cage” on the subjects analysed, assumes the affective origin of language, and thought. Indeed, it is the feeling of the “lack” of the pathic dimension of experience within contemporary society that leads Boissière to focus on the “living” dimension of the experience of playing (le “vivant” du jeu), in a way that rehabilitates this dimension from the very way in which the philosophical study of it is carried out. This begins with a way of writing – characterised by the use of the first person and other stylistic choices – through which she “claim[s] the necessity” of a way of doing philosophy that is not “guided by rational argumentation”, but by the “situated” nature of the reflexive and writing experience – an experience that includes that of being “a woman in a theoretical universe, that of philosophy, that is almost exclusively shaped by men”.
Keywords: Anne Boissière, L’Art et le vivant du jeu, book review